Geopolitically induced investments in biofuels - Brutschin, Elina; Fleig, Andreas (Energy economics, 2018)
While supply disruptions of oil imports are widely considered a serious threat to a country's energy and overall national security, systematic investigations into the effects of security concerns on investments in energy technology are rare. Complementing existing energy policy literature, this paper investigates the impact of conflict involvement of major oil suppliers on RD&D expenditures in biofuels among import-dependent economies, i.e. geopolitically induced investments. Utilizing the recently released data set on Integrated Crisis Early Warning System (ICEWS), our sample comprises information on 12 EU member states from 1997 to 2014. Among those we find that RD&D expenditures in biofuels are positively associated with the conflict involvement of the respective country's major oil supplier. The results are robust across different model specifications and measurements of conflict. We argue that joining arguments from political economy and conflict research can help to explain the heterogeneous pattern of investments in energy technology in resource-poor European countries. In addition, it increases our understanding of innovation activities within the energy sector.
Gesehen am 17.10.2019